Metal-Free Iodoperfluoroalkylation: Photocatalysis versus Frustrated Lewis Pair Catalysis - Helmecke, Lucas; Spittler, Michael; Schmidt, Bernd M.; Czekelius, Constantin (Synthesis, 2021)
A comparison of two catalytic, metal-free iodoperfluoroalkylation protocols is presented. Frustrated Lewis pairs [tBu3P/B(C6F5)3] or phosphines/phosphites under visible light irradiation efficiently mediate the functionalization of non-activated alkenes and alkynes. A comprehensive account of the corresponding substrate scopes as well as insights into the mechanistic details of both reaction pathways are provided.
Keywords: iodoperfluoroalkylation; frustrated Lewis pair; electron donor–acceptor complex; halogenations; radicals